Confirmation and Characterization of the Eccentric, Warm Jupiter TIC 393818343 b with a Network of Citizen Scientists - Sgro, LA; Dalba, PA; Esposito, TM; Marchis, F; Dragomir, D; Villanueva, S; Fulton, B; Billiani, M; Loose, M; Meneghelli, N; Rivett, D; Saibi, F; et al. (IOP Publishing, 2024)
NASA’s Transiting Exoplanet Survey Satellite (TESS) has identified over 7000 candidate exoplanets via the transit method, with gas giants among the most readily detected due to their large radii. Even so, long intervals between TESS observations for much of the sky lead to candidates for which only a single transit is detected in one TESS sector, leaving those candidate exoplanets with unconstrained orbital periods. Here, we confirm the planetary nature of TIC 393818343 b, originally identified via a single TESS transit, using radial velocity data and ground-based photometric observations from citizen scientists with the Unistellar Network and Exoplanet Watch. We determine a period of P = 16.24921 −0.00011+0.00010 days, a mass M P = 4.34 ± 0.15 M J, and semimajor axis a = 0.1291 −0.0022+0.0021 au, placing TIC 393818343 b in the “warm Jupiter” population of exoplanets. With an eccentricity e = 0.6058 ± 0.0023, TIC 393818343 b is the most eccentric warm Jupiter to be discovered by TESS orbiting less than 0.15 au from its host star and therefore an excellent candidate for follow-up, as it may inform our future understanding of how hot and warm Jupiter populations are linked.